Designer Leptin Receptor Antagonist Allo-aca Inhibits VEGF Effects in Ophthalmic Neoangiogenesis Models - Coroniti, Roberta; Farjo, Rafal; Nuno, Didier J.; Otvos, Laszlo; Scolaro, Laura; Surmacz, Eva (Frontiers in Molecular Biosciences, 2016)
Experimental and clinical data suggest that pro-angiogenic, pro-inflammatory and mitogenic cytokine leptin can be implicated in ocular neovascularization and other eye pathologies. At least in part, leptin action appears to be mediated through functional interplay with vascular endothelial growth factor (VEGF). VEGF is a potent regulator of neoangiogenesis and vascular leakage with a proven role in conditions such as proliferative diabetic retinopathy, age-related macular degeneration and diabetic macular edema. Accordingly, drugs targeting VEGF are becoming mainstream treatments for these diseases. The crosstalk between leptin and VEGF has been noted in different tissues, but its involvement in the development of eye pathologies is unclear. Leptin is coexpressed with VEGF during ocular neovascularization and can potentiate VEGF synthesis and angiogenic function. However, whether or not VEGF regulates leptin expression or signaling has never been studied. Consequently, we addressed this aspect of leptin/VEGF crosstalk in ocular models, focusing on therapeutic exploration of underlying mechanisms. Here we show, for the first time, that in retinal (RF/6A) and corneal (BCE) endothelial cells, VEGF (100 ng/mL, 24 h) stimulated leptin mRNA synthesis by 70 and 30%, respectively, and protein expression by 56 and 28%, respectively. In parallel, VEGF induced RF/6A and BCE cell growth by 33 and 20%, respectively. In addition, VEGF upregulated chemotaxis and chemokinesis in retinal cells by ~40%. VEGF-dependent proliferation and migration were significantly reduced in the presence of the leptin receptor antagonist, Allo-aca, at 100-250 nmol/L concentrations. Furthermore, Allo-aca suppressed VEGF-dependent long-term (24 h), but not acute (15 min) stimulation of the Akt and ERK1/2 signaling pathways. The efficacy of Allo-aca was validated in the rat laser-induced choroidal neovascularization model where the compound (5 μg/eye) significantly reduced pathological vascularization with the efficacy similar to that of a standard treatment (anti-VEGF antibody, 1 μg/eye). Cumulatively, our results suggest that chronic exposure to VEGF upregulates leptin expression and function. As leptin can in turn activate VEGF, the increased abundance of both cytokines could amplify pro-angiogenic and pro-inflammatory environement in the eye. Thus, combined therapies targeting ObR and VEGF should be considered in the treatment of ocular diseases.